Integrating dual evaluation and FLUS model for land use simulation and urban growth boundary delineation in production-living-ecology spaces: a case study of Central Harbin, China - Ting Zhang; Shuang Liu; Mengyao Wang; Haihui Hu; Yuzhu Hu (Geocarto International)
The delineation of Urban Growth Boundaries (UGBs) has been effective in curbing urban sprawl and facilitating sustainable urban development. This research employs an interdisciplinary framework that combines landscape architecture, landscape ecology, and GIS, focusing on Harbin—a typical cold-region city. The results are as follows: (1) The land use simulation demonstrated high reliability, achieving an average accuracy of 0.955 and Kappa coefficients exceeding 0.8, validating the projected urban growth boundaries for Harbin’s central urban area by 2035. (2) Distinct urban growth boundaries were evident under different development scenarios. (3) Evaluations showed that development scenarios prioritizing living and production spaces had better landscape integration. (4) All development scenarios were proximate to the existing built-up areas of the central urban region. This study not only confirms the utility of the FLUS model in accurately simulating urban land use changes but also provides actionable insights for urban expansion strategies in Northeast China’s cold-region cities.